Application of the TROPOS Method to Development a Website-Based Blood Stock Management System at Palang Merah Indonesia (PMI) in Bandung City - Rinda Firma Violita; Sri Widowati; Prati Hutari Gani (ISB Atma Luhur, 2020)
Palang Merah Indonesia (PMI) is a social organization in the city of Bandung. In the business process, the blood donor section has not used any software that satisfies the need to connect communities and PMI on blood donor information. So it takes software that can help the process of running blood donor business to minimize the problems that occur such as human error and not spread information about blood supply. RE (Requirement Engineering) is an early stage as an important task, as many software failures come from inconsistent, incomplete or just wrong specification requirements. In RE there is a process that is requirement analysis to do analysis of user needs. Goal Oriented Requirements Engineering (GORE) is one of the models that can be used to analyse user needs. One method on the GORE model is the TROPOS method. The use of TROPOS on the development of the blood stock management software to focus on the needs analysis on the stages of modeling early requirement and late requirement. The results of the analysis are implemented into web software design. Software that has been created based on the modeling evaluated using BlackBox Testing with user acceptance test (UAT) by stakeholders. Based on the results of the assessment UAT score, the results of the respondents assessment is 3.55%, so that the blood stock management software can be used as a supporting tool to run the blood stock business process of PMI.